Physiologic Effects of Instilled and Aerosolized Surfactant Using a Breath-Synchronized Nebulizer on Surfactant-Deficient Rabbits - Robert M. DiBlasi; Kellie J. Micheletti; Joseph D. Zimmerman; Jonathan A. Poli; James B. Fink; Masaki Kajimoto (MDPI AG, 2021)
Surfactant administration incorporates liquid bolus instillation via endotracheal tube catheter and use of a mechanical ventilator. Aerosolized surfactant has generated interest and conflicting data related to dose requirements and efficacy. We hypothesized that aerosolized surfactant with a novel breath-actuated vibrating mesh nebulizer would have similar efficacy and safety as instilled surfactant. Juvenile rabbits (1.50 ± 0.20 kg, n = 17) were sedated, anesthetized, intubated, and surfactant was depleted via lung lavage on mechanical ventilation. Subjects were randomized to receive standard dose liquid instillation via catheter (n = 5); low dose surfactant (n = 5) and standard dose surfactant (n = 5) via aerosol; and descriptive controls (no treatment, n = 2). Peridosing events, disease severity and gas exchange, were recorded every 30 min for 3 h following surfactant administration. Direct-Instillation group had higher incidence for peridosing events than aerosol. Standard dose liquid and aerosol groups had greater PaO2 from pre-treatment baseline following surfactant (p < 0.05) with greater ventilation efficiency with aerosol (p < 0.05). Our study showed similar improvement in oxygenation response with greater ventilation efficiency with aerosol than liquid bolus administration at the same dose with fewer peridosing events. Breath-synchronized aerosol via nebulizer has potential as a safe, effective, and economical alternative to bolus liquid surfactant instillation.